Implementation Of Good Governance In Appointments To State Civil Apparatus Positions In Mamberamo Raya Regency - Isak Bonai; Udaya Madjid; Faria Ruhana (Jurnal Scientia, 2024)
A bureaucracy that adheres to the principles of governance is one that complies with the principles of law and justice. The placement of civil servants in high-level leadership positions and administrative positions generally has not applied the principles of good governance. This conclusion is based on data obtained by researchers from a Pre-survey conducted within the Mamberamo Raya Regency Government. Researchers found inconsistencies between civil servants occupying high-level managerial positions and administrative managerial positions with their educational background, knowledge, rank/grade that are not suitable for their assigned positions. Therefore, the issue addressed by this researcher is why the placement of civil servants in high-level managerial positions and administrative managerial positions within the Mamberamo Raya Regency Government has not adhered to the principles of good governance. The aim of this research is to apply the principles of good governance, namely accountability, transparency, and adherence to legal regulations, in the placement of high-level managerial positions and administrative managerial positions within the Mamberamo Raya Regency Government. The research approach employed is Qualitative Descriptive. Data is collected through observation, interviews, and documentation. The research findings indicate that out of the three focuses used, namely accountability, transparency, and adherence to legal regulations, the principles of transparency and adherence to legal regulations have not been fully implemented. This is because loyalty and closeness to the leadership become one of the means or reasons and considerations in the decision-making process of appointing individuals to positions, both in high-level managerial positions and administrative managerial positions. The Job and Rank Deliberation Body, as well as its membership (BAPERJAKAT), only provides input, suggestions, and considerations in the appointment process, while the final decision lies solely with the regional head.